Development of Breeding Works in Cattle Farming (In the Example of Surkhandarya) - Jumaeva Shohida Chorievna (Researchparks Publishing, 2022)
In the article, in the Surkhandarya oasis, the work carried out on increasing the productivity of cattle breeding to meet the needs of the population for livestock products, that is, meat and dairy products, its development, the activities of farms in the field of livestock breeding, the establishment of breeding, information is provided on the rapid development of breeding work in cattle breeding.